2004
DOI: 10.1242/jcs.01119
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in traction forces with DC electric field in osteoblast-like cells

Abstract: Primary bovine osteoblasts and human osteosarcoma cells exposed to direct-current electric fields undergo processes of retraction and elongation ultimately resulting in the realignment of the long cellular axis perpendicular to the electric field. The time taken for this reorientation was inversely correlated to field strength within a certain range. Cellular force output during reorientation was analyzed using a simple modification of traction force microscopy. The first detectable reaction was an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 48 publications
5
43
0
Order By: Relevance
“…Cells have been known to reorient in vitro in response to stimuli such as fluid shear stress, multi-directional cyclical stretch, and electrical fields [24][25][26]. Cell reorientation due to rapid topographical changes, to our knowledge, has not been previously shown.…”
Section: Resultsmentioning
confidence: 80%
“…Cells have been known to reorient in vitro in response to stimuli such as fluid shear stress, multi-directional cyclical stretch, and electrical fields [24][25][26]. Cell reorientation due to rapid topographical changes, to our knowledge, has not been previously shown.…”
Section: Resultsmentioning
confidence: 80%
“…Common parameters applied include fixed currents of 1-50 ”A/ cm 2 , which can affect osteoblast proliferation and expression of differentiation markers (Bodamyali et al, 1999;Kim et al, 2006). The majority of published studies of in vitro DC stimulation used electrodes submerged in the tissue culture medium, establishing a DC electric field and inducing electrochemical currents between the anode and the cathode (Curtze et al, 2004;Ercan and Webster, 2008). However, the products generated at the cathode and the anode that have enhancing or detrimental effects on cell response, respectively (Black et al, 1984;Bodamyali et al, 1999), may obscure the results of DC electrical stimulation.…”
Section: Direct Current (Dc) Stimulationmentioning
confidence: 99%
“…However, in Sun's study, the strong electrical strength (7 V/cm and 10 V/cm) failed to induce any significant MSC reorientation. Curtze et al (Curtze et al, 2004) used agar bridges to induce ES to cells cultured on either cover slips or collagen-coated polyacrylamide gels. They observed that primary bovine osteoblasts and human osteosarcoma cells exposed to a DC EF of 10 V/cm realigned themselves with their long axis perpendicular to the EF.…”
Section: Salt Bridgementioning
confidence: 99%